Morphotectonic Analysis of Wadi Al-Batin Alluvial Fan, South of Iraq, Using Remote Sensing and GIS Techniques - Albhadili, Suaad; Almallah, Inass; Almulla, Saher (Iraqi Journal of Science, 2023)
This research aimed to know the tectonic activity of the Wadi Al-Batin alluvial fan using hydrological and morphotectonic analyses. Wadi Al-Batin alluvial fan is deposited from Wadi Al-Rimah in Saudi Arabia, which extended to Iraqi and Kuwait international boundaries. The longitudinal and transverse faults that characterize this region were common. The Abu- Jir-Euphrates faults have a significant impact on the region. The faults zone consists of several NW- SE trending faults running from the Rutba in western Iraq to the south along the Euphrates through Kuwait and meeting the Al-Batin fault to the Jal Al-Zor fault. The Hydromorphometric analysis of the present fan shows five watersheds having asymmetry shapes, more elongated and activity from the elongation ratio and asymmetry factor values. In contrast, transverse topographic symmetry and mountain front sinuosity factor have moderate to low activity from the stream length gradient index. The morphotectonic analysis suggests that the Wadi Al-Batin alluvial fan has a moderate tectonic activity due to the tectonic activity of the subsurface lineaments and the oil field activities found in the region.